The Role of Corporations in Achieving Ecological Sustainability - Shrivastava, Paul (Academy of Management Review, 1995)
Ecological problems rooted in organizational activities have increased significantly, yet the role corporations play in achieving ecological sustainability is poorly understood. This article examines the implications of ecologically sustainable development for corporations. It articulates corporate ecological sustainability through the concepts of (a) total quality environmental management, (b) ecologically sustainable competitive strategies, (c) technology transfer through technology-for nature-swaps, and (d) reducing the impact of populations on ecosystems. It examines the implications that these concepts have for organizational research.